Ursolic acid derivative UAOS-Na treats experimental autoimmune encephalomyelitis by immunoregulation and protecting myelin - Wang, Maolin; Gu, Chenming; Yang, Yifu; Chen, Liang; Chen, Kaixian; Du, Jun; Wu, Huali; Li, Yiming (Frontiers in Neurology, 2023)
Multiple sclerosis (MS) is an inflammatory demyelinating disease of the central nervous system (CNS). Ursolic acid (UA) can be used in the MS treatment with anti-inflammatory and neuroprotective activities. However, UA is insoluble in water, which may affect its medication effectiveness. In our research, we evaluated the pharmacological effects of UAOS-Na, a water-soluble derivative of UA, on experimental autoimmune encephalomyelitis (EAE) mouse, explored its underlying mechanism, and verified the mechanism by in vitro and in vivo experiments. As we expected, UAOS-Na (30 mg/kg/d) delayed the onset time of EAE from 11.78 days post immunization (dpi) to 14.33 dpi, reduced the incidence from 90.0% to 42.9%. UAOS-Na (60 mg/kg/d) significantly reduced the serum levels of IFN-γ, IL-17A, TNF-α and IL-6, reduced the mononuclear cell infiltration of spinal cord, and inhibited the overexpression of key transcription factors T-bet and ROR-γt of EAE mouse spinal cord. In addition, UAOS-Na attenuated demyelination and astrogliosis in the CNS of EAE and cuprizone-induced mice. Mechanistically, proteomics showed that 96 differential expression proteins (DEPs) were enriched and 94 were upregulated in EAE mice compared with normal group. After UAOS-Na treatment, 16 DEPs were enriched and 15 were downregulated, and these DEPs were markedly enriched in phagosome, MAPK, and antigen processing and presentation (APP) signaling pathway, etc. Among them, there were few studies on APP signaling pathway related with MS. Therefore, we further investigated the effect of UAOS-Na on APP signaling pathway and found that UAOS-Na downregulated the protein levels of Tapbp and H2-T23 in MHC-I antigen presentation pathway and reduced the proliferation of splenic CD8 T cells, thereby inhibiting the CNS infiltration of CD8 T cells. Together, our findings demonstrated that UAOS-Na have both myelin protective and anti-inflammatory effects. And it could reduce the inflammation of MS by downregulating the expression of Tapbp and H2-T23 in the MHC-I antigen presentation pathway.